Bargaining for fiscal control: Tax federalism in Brazil and Mexico, 1870-1940 - André Martínez Fritscher (Banco de México, 2011)
This paper studies the historical origins of the federalist institutions in Mexico and Brazil. Using a bargaining game model, I argue that the type of commodities each country produced by the end of the nineteenth Century determined the negotiation power of local governments. This led to the buildup of opposite federalist institutions in both countries, which have persisted until nowadays. The model shows that countries with regions with more autonomy to produce and trade their commodities increase the local power to collect more taxes. While in Brazil coffee was the most important commodity, Mexico relied on mining products. Coffee was produced by local landowners who became economically powerful and they were able that export taxes were collected locally with the proclamation of the 1891 Constitution. Empirical estimates show that, after 1891, exporter states increased significantly their own fiscal revenue. On the other hand, mining was capital and technology intensive, inputs that were domestically scarce in Mexico. To finance those activities foreign investment was promoted centrally, weakening the relative power of local elites.
Keywords: H71; H77; N46; N96; 330; Institutions; Fiscal Federalism; Public Finance and Endowments; Finanzgeschichte; Finanzbeziehungen; Verhandlungstheorie; Brasilien; Mexiko